2003
DOI: 10.1039/b212628a
|View full text |Cite
|
Sign up to set email alerts
|

The photophysics of fac-[Re(CO)3(dppz)(py)]+ in CH3CN: a comparative picosecond flash photolysis, transient infrared, transient resonance Raman and density functional theoretical study

Abstract: The photophysical properties of fac-[Re(CO)3(dppz)(py)]+ (1, where dppz = dipyrido[3,2-a: 2',3'-c]phenazine) in CH3CN have been investigated using a series of complementary techniques including visible and infrared transient absorption and resonance Raman spectroscopy on the picosecond and nanosecond timescales. The results confirm previous reports that the lowest-lying emissive state in 1 is a triplet intra-ligand (3IL) state localised on the dppz ligand and have provided detailed information on the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 64 publications
(75 reference statements)
10
87
1
2
Order By: Relevance
“…The down-shift in the energies of the transient bands from the ground-state positions is typical of ππ* 3 IL(dppz) excited states. 1923,26,27,54 Tentatively, we attribute the initially formed 2026 and 1908 cm −1 transient bands to a hot 3 IL state localized at the phen part of the dppz ligand, 3 IL(phen). Subsequent electron density reorganization and cooling produce another 3 IL state localized predominantly at the phenazine part, 3 IL(phz), manifested as the sharp 2036 cm −1 band.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The down-shift in the energies of the transient bands from the ground-state positions is typical of ππ* 3 IL(dppz) excited states. 1923,26,27,54 Tentatively, we attribute the initially formed 2026 and 1908 cm −1 transient bands to a hot 3 IL state localized at the phen part of the dppz ligand, 3 IL(phen). Subsequent electron density reorganization and cooling produce another 3 IL state localized predominantly at the phenazine part, 3 IL(phz), manifested as the sharp 2036 cm −1 band.…”
Section: Resultsmentioning
confidence: 84%
“…In the absence of DNA, negligible emission is observed from an aqueous solution of Re′-OH or Re′-OEt; however, in the presence of AT-30 and in the Re-25(I) sample, a prominent emission band is observed that exhibits a maximum at 570 nm and a shoulder near 600 nm, resembling the emission spectrum seen for similar Re complexes in organic solvents. 19,21,22,41,42,57,65 By comparison with the emission of [Ru(bpy) 3 ] 2+ in deaerated acetonitrile, the emission quantum yield of Re′-OEt in the presence of AT-30 in buffer is 0.008 (compared to 0.062 for [Ru(bpy) 3 ] 2+ ). 73 In the presence of GC-30 and in the Re-25(G) sample, the emission is much less intense, the maxima are shifted to 585 nm, and no shoulder is observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Re I carbonyl diimine complexes are mostly photostable and suitable as sensors or switches. [4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In rare cases, [23,24] some of which will be discussed below, the lowest excited state is localized on the ligand X and isomerization may ensue after its population.…”
Section: A C H T U N G T R E N N U N G (Bpy)]mentioning
confidence: 99%
“…[92] The nature of the lowest excited states of several dppz-complexes have been identified using TRIR spectroscopy on the picosecond timescale. [40][41][42][43][44][45][46][47]93] American Chemical Society.…”
Section: Time-resolved Infrared Spectroscopymentioning
confidence: 99%